Products of Toeplitz Operators on the 2-Analytic Bergman Space. (4th October 2021) - Zhang, Bo; Yang, Yixin; Lu, Yufeng
Abstract : Let f and g be bounded functions, and let T f and T g be Toeplitz operators on A 2 2 D . We show that if the product T f T g equals zero and one of f and g is a radial function satisfying a Mellin transform condition, then the other function must be zero.